If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m(5m + -19) = -12 Reorder the terms: m(-19 + 5m) = -12 (-19 * m + 5m * m) = -12 (-19m + 5m2) = -12 Solving -19m + 5m2 = -12 Solving for variable 'm'. Reorder the terms: 12 + -19m + 5m2 = -12 + 12 Combine like terms: -12 + 12 = 0 12 + -19m + 5m2 = 0 Factor a trinomial. (4 + -5m)(3 + -1m) = 0Subproblem 1
Set the factor '(4 + -5m)' equal to zero and attempt to solve: Simplifying 4 + -5m = 0 Solving 4 + -5m = 0 Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -5m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -5m = 0 + -4 -5m = 0 + -4 Combine like terms: 0 + -4 = -4 -5m = -4 Divide each side by '-5'. m = 0.8 Simplifying m = 0.8Subproblem 2
Set the factor '(3 + -1m)' equal to zero and attempt to solve: Simplifying 3 + -1m = 0 Solving 3 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1m = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1m = 0 + -3 -1m = 0 + -3 Combine like terms: 0 + -3 = -3 -1m = -3 Divide each side by '-1'. m = 3 Simplifying m = 3Solution
m = {0.8, 3}
| 1/t-1/(2t)-1/(5t)=10/(t+1) | | x-5=(x+9)3 | | t^2+1/2t+1/16 | | 8x+4-4x=x-14 | | 5x^2-15x+50=0 | | 17.28=(1.41)+0.68 | | 3(p-2)-7p=6 | | 0=2x^3-6x^2-5x-15 | | 1/t-1/2t-1/5t=10/t+1 | | 500^3/10 | | 6x^3-10x^2+2x=0 | | 5/6t+2=4/3t+3/2 | | 3p-6-7p=6 | | 25r^2=5r | | 6+5i/-2i | | (x-5)/3=x+9 | | -3++4=19 | | a+9a= | | -76-32= | | p=2(6+22) | | 24-10y=39 | | 7/6=5/x | | (5w-4)(6+w)=0 | | (5x+2y-16)2= | | 8r-5-9r=4+r-6 | | -10a=40 | | 2/3a+5/6=-5/18a+1/2+1/18a | | -1/20+7/10= | | p=29(6+22) | | 12-8x-4x^2=0 | | z+z-10=3 | | 2x+7-5(x+1)=4x+8 |